Composite least mean fourth algorithm (CLMF) based dynamic voltage restorer for enhancement of power quality - Kiran, Tummala Kranti; Rajagopal, Balakrishnan; Raju, Yerramilli Butchi (Institute of Advanced Engineering and Science, 2025)
This paper introduces the composite least mean fourth control algorithm (CLMF) with a dynamic voltage restorer (DVR) to address power quality problems linked to voltage at the source side and supply clean voltage to the distribution network's sensitive loads. The performance of the two least mean fourth adaptive filters combined convexly by this control technique is better than that of the filters working independently. When comparing the suggested control to conventional synchronous reference frame-based vector control, phase-locked loops, abc to dq transformations, and dq to abc transformations are all practically eliminated. When compared to standard least mean square (LMS) and least mean fourth (LMF) control approaches, the proposed CLMF's features—simple computation, ease of implementation, reduced settling time, and increased reliability—show that the suggested controller is more efficient. The proposed CLMF controller excels in terms of rise time, 0.082 sec., and less settling time, 0.092 sec., respectively, with a peak overshoot of 2.33% compared with the aforementioned control algorithms. Different voltage-related PQ issues have been corrected successfully by the proposed CLMF. Through simulation using MATLAB/Simulink, system performance has been verified.